"역함수를 이용한 치환적분"의 두 판 사이의 차이
둘러보기로 가기
검색하러 가기
(피타고라스님이 이 페이지를 개설하였습니다.) |
|||
1번째 줄: | 1번째 줄: | ||
+ | <math>\int f(x)\,dx=xf(x)-\int xf'(x)\,dx+xf(x)-\int f^{-1}(f(x))f'(x)\,dx+xf(x)-G(f(x))</math><br> | ||
+ | 여기서 <math>G(x)= \int f^{-1}(x)\,dx</math> | ||
+ | |||
+ | |||
+ | |||
+ | 문제 | ||
+ | |||
+ | <math>\int \sqrt{\frac{x}{1-x}}\,dx</math> | ||
+ | |||
+ | <math>G(x)=\int f^{-1}(x)\,dx= \int\frac{x^2}{1+x^2}\,dx=\int(1-\frac{1}{1+x^2})\,dx=x-\arctan x+C</math><br> | ||
+ | |||
+ | 따라서, <br> | ||
+ | |||
+ | <math>\sqrt{\frac{x}{1-x}}\,dx=(x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C</math> | ||
+ | |||
+ | <math>\int \sqrt{\frac{x}{1-x}}\,dx= (x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C</math> |
2009년 8월 22일 (토) 20:02 판
\(\int f(x)\,dx=xf(x)-\int xf'(x)\,dx+xf(x)-\int f^{-1}(f(x))f'(x)\,dx+xf(x)-G(f(x))\)
여기서 \(G(x)= \int f^{-1}(x)\,dx\)
문제
\(\int \sqrt{\frac{x}{1-x}}\,dx\)
\(G(x)=\int f^{-1}(x)\,dx= \int\frac{x^2}{1+x^2}\,dx=\int(1-\frac{1}{1+x^2})\,dx=x-\arctan x+C\)
따라서,
\(\sqrt{\frac{x}{1-x}}\,dx=(x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C\)
\(\int \sqrt{\frac{x}{1-x}}\,dx= (x-1)\sqrt{\frac{x}{1-x}}+\arctan{\sqrt{\frac{x}{1-x}}}+C\)